Access Programs for Health and Social Services in the English Language : Presentation to NPIs - Prata, Ghislaine (2019)

Annual Report 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Assessment of the Priority Setting Process for the English-speaking Communities of Quebec (ESCQ) : Guide for the Focus Groups - Canada. Department of Canadian Heritage; Quebec Community Groups Network (QCGN); KSAR & Associates (2019)

Innovation in Action / Innovation en action - Quebec Community Groups Network (QCGN) (2019)
The Community Innovation Fund (CIF) has helped Quebec’s English- speaking communities transform social innovation into action through the development of skills. The Fund financed 10 innovative projects that targeted particular needs and priorities of vulnerable English-speaking youth, seniors and newcomers. Each project, in its own way, served to improve job skills or help maintain basic socio-economic security of English-speaking Quebecers. In the following pages, you will learn more about these projects – what they set out to do, what they’ve accomplished and how they served to enhance the vitality of English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2018-2019 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

English-speaking Communities of the Gaspésie-Îles-de-la-Madeleine : A Regional Profile - Vision Gaspé-Percé Now (VGPN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Main Achievements 2014-2018 - Dialogue McGill (2018)

Profil des rélisations 2014-2018 - Dialogue McGill (2018)

Annual Report : 2017-2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

The Network Model : Influencing Public Policy for Social Change - Community Health and Social Services Network (CHSSN) (2017)
The case studies being presented in today demonstrate that the development principles are at work every day and are now being pressed into new areas of action. The values underpinning the network model include promoting the identity of our communities, promoting social inclusion and advocating for equity in the broader society in its treatment of communities. These values can support network strategies to enter the “next level” of participation in societal initiatives setting broad policy goals. The reward for such effort can be societal recognition that the programs that define Quebec’s commitment to social progress also include our communities.

2016-2017 Funded Projects - Dialogue McGill (2017)

Projets financés 2016-2017 - Dialogue McGill (2017)

Annual Report : 2016-2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

QCGN Appearance before the House of Commons Standing Committee on Official Languages - Quebec Community Groups Network (QCGN) (2016)

Network News - Quebec Community Groups Network (QCGN) (2016)

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2016)
Health promotion is an activity that community organizations can adopt to enhance visibility and credibility in their communities. Health promotion activities can respond to real needs of different groups and create opportunities to engage the public system with the community organization and the constituencies it serves. For the public network, a community organization that has established a health promotion role has the potential to become a prime partner in helping an institution better serve its target population. In recent years, community networks have developed health promotion programs that have reached thousands of community members and can now demonstrate positive results. The Forum will discuss how this development is resulting in promising and best practices, and inspiring a range of public and community interests to engage in health promotion for English-speaking communities.

2015-2016 Funded Projects - Dialogue McGill (2016)

Projets financés 2015-2016 - Dialogue McGill (2016)

Ahuntsic Cartierville : English-speaking Population 2016 / Ahuntsic Cartierville : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Anjou : English-speaking Population 2016 / Anjou : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Annual Report : 2015-2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Mercier Hochelaga-Maisonnneuve : English-speaking Population 2016 / Mercier Hochelaga-Maisonnneuve : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Montréal-Nord : English-speaking Population 2016 / Montréal-Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rivière-des-Prairies and Pointe-aux-Trembles : English-speaking Population 2016 / Rivière-des-Prairies and Pointe-aux-Trembles : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie l'Est : English-speaking Population 2016 / Rosemont-La Petite-Patrie-l-est : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie Nord : English-speaking Population 2016 / Rosemont La Petite-Patrie Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Laurent : English-speaking Population 2016 / Saint-Laurent : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Léonard : English-speaking Population 2016 / Saint-Léonard : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Villeray–Saint-Michel–Parc-Extension : English-speaking Population 2016 / Villeray–Saint-Michel–Parc-Extension : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Focus Group Findings 2015-2016 - Seniors Action Quebec (SAQ) (2016)

2017-2018 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Strategic Priorities Forum (Quebec Community Groups Network (QCGN), 2016)
In September 2011, the Quebec Community Groups Networks launched The Strategic Priorities Forum, a standing five-year cyclical process to identify common priorities ensuring a vital and sustainable future for Quebec’s English-speaking communities and to collectively pursue enabling strategies to achieve community goals over five years. In this capacity, the QCGN established a nine-member Priority Setting Steering Committee (PSSC), a permanent Committee of QCGN’s Board of Directors, to assist the community with the governance of the Strategic Priorities Forum.

La communauté d'expression anglaise de la [de la] grande région de Québec - Voice of English-speaking Quebec (VEQ) (2016)

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report - Qu'anglo (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report : Executive Summary - Qu'anglo (2015)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

2014-2015 Funded Projects - Dialogue McGill (2015)

Projets financés 2014-2015 - Dialogue McGill (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)

Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Mesure 2 : Programme de maintien en poste : Volets Réseaux communautaires et Maisons d’enseignement : Prospectus 2014-2018 - Dialogue McGill (2014)
Le Projet de formation et de maintien en poste des professionnels de la santé de l’Université McGill contribue aux initiatives du Québec destinées à assurer aux Québécois d’expression anglaise l’accès dans leur langue à la gamme complète de services de santé et de services sociaux, et ce, au moyen de diverses mesures visant à fournir et à maintenir en poste un complément de main-d’œuvre suffisant, capable d’offrir des services en anglais. Le projet constitue un outil additionnel favorisant l’application et la bonification des programmes régionaux d’accès aux services de santé et aux services sociaux en langue anglaise, conformément à la Loi sur les services de santé et les services sociaux. Ce Projet a pour objectifs précis de susciter des initiatives de formation et de maintien en poste qui fourniront aux professionnels de la santé et des services sociaux l’occasion d’améliorer leur capacité d’offrir des services en anglais, ainsi que l’occasion de travailler là où ils seront en mesure de répondre aux besoins des populations d’expression anglaise du Québec. Le Projet vise également à promouvoir la recherche et le partage de l’information quant aux approches visant à réduire les barrières en matière d’accès aux services de santé et aux services sociaux pour les Québécois d’expression anglaise.

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

Community in Movement Forum - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Annual Report : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Rapport Annuel : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Report : Future Forum of the English-speaking Community - Future Forum of the English-speaking Community (Voice of English-speaking Quebec (VEQ), 2013)
The Future Forum was held on November 24th, 2012 from 9 am - 2 pm at Eastern Québec Learning Center in Quebec City, Québec. The purpose of the event was to share opinions on the current state, needs and challenges of the English-speaking community while generating a shared vision for our future.

Annual Report : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

Rapport Annuel : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Annual Report : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Rapport Annuel : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Community Health Education Program (CHEP) : 2010-2011 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2011)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

Community Health Education Program (CHEP) : 2009-2010 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2010)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)